2016
DOI: 10.1107/s2059798316000954
|View full text |Cite
|
Sign up to set email alerts
|

Automated harvesting and processing of protein crystals through laser photoablation

Abstract: New methods for crystal mounting, soaking and cryocooling contribute to bridging the automation gap between crystallization and X-ray data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 47 publications
1
87
0
1
Order By: Relevance
“…2). Pellegrini and coworkers showed that several crystals (solvent content 44-47%) could be successfully flash-cooled simply by wicking away all external solution (Pellegrini et al, 2011), an approach that has been adopted for automounting of crystals (Zander et al, 2016). Our results suggest that some of these crystals may still benefit from solvent-contraction optimization.…”
Section: Thermal-contraction-guided Cryo-optimizationmentioning
confidence: 70%
See 1 more Smart Citation
“…2). Pellegrini and coworkers showed that several crystals (solvent content 44-47%) could be successfully flash-cooled simply by wicking away all external solution (Pellegrini et al, 2011), an approach that has been adopted for automounting of crystals (Zander et al, 2016). Our results suggest that some of these crystals may still benefit from solvent-contraction optimization.…”
Section: Thermal-contraction-guided Cryo-optimizationmentioning
confidence: 70%
“…For example, Warkentin and Thorne showed that thaumatin crystals grown from 1.5 M sodium potassium tartrate could be both flash-cooled and slow-cooled simply by using NVH oil and carefully removing all aqueous external solvent (Warkentin & Thorne, 2009). Pellegrini and coworkers showed that several crystals (solvent content 44-47%) could be successfully flash-cooled simply by wicking away all external solution (Pellegrini et al, 2011), an approach that has been adopted for automounting of crystals (Zander et al, 2016). The cell contraction in this case was about 4%, corresponding to a solvent contraction of about 7% (Fig.…”
Section: Thermal-contraction-guided Cryo-optimizationmentioning
confidence: 99%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/236596 doi: bioRxiv preprint first posted online developments in the robotic mounting and soaking of crystals (Zander, Hoffmann, et al, 2016) we envision that the future of macromolecular crystallography is the provision of a fully automated high throughput service able to rapidly produce high quality structural models and screen for potential therapeutic and probe molecules.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Tony Warne (MRC-LMB, Cambridge, UK) for the gift of (Zander, Hoffmann, et al, 2016) support that has 3 crystals mounted. The widest orientation of the mount was selected.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…While no crystals could be obtained for the wildtype and most of the mutants, one of these variants produced crystals very efficiently in the absence of myricetin. 30 In this variant, Ala141 was substituted by Phe (A141F, PDB code: 5AMW). Ala 141 is located in the predicted α-helix 3 (Supprting Information Figure 1A) which, based on the structure of Fra a 1.01E and Fra a 1.03, faces the cavity.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%